A preliminary study on the effectiveness of new students’ adjustment to university / Normala Ismail and Mohamad Kamil Ariff Khalid - Ismail, Normala; Khalid, Mohamad Kamil Ariff (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Adjustment among new students at the university plays an important role in determining their success at university. This study showed one of the reasons students fail to complete their study is due to adjustment problems. Students found to be unable to deal with the challenges and demands on campus and experience a variety of problems that some of them failed to proceed to the next semester. The population of the study consist of 143 First Semester Diploma students in the Faculty of Business and Management studies at Universiti Teknologi MARA Pahang Raub Campus. The instrument used is questionnaires. There are four subscales designed to measure the effectiveness of student adjustment to university that are academic adjustment, social adjustment, personal (emotional) adjustment and institutional commitment. The study shows that adaptability on campus has a relationship with psychosocial abilities possessed by the students. Among the psychosocial abilities have a positive and significant impact on student adjustment is emotional intelligence, coping, and social support. All three of these psychosocial capabilities found to play an important role in helping students adjust at the university. Thus, the university must take proactive steps to develop emotional intelligence, coping and social support among new students to improve their adaptability.